2014
DOI: 10.1021/jp505544y
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Computationally Efficient Prediction of Thermochemical Properties of Biomolecules Using the Generalized Connectivity-Based Hierarchy

Abstract: In this study we have used the connectivity-based hierarchy (CBH) method to derive accurate heats of formation of a range of biomolecules, 18 amino acids and 10 barbituric acid/uracil derivatives. The hierarchy is based on the connectivity of the different atoms in a large molecule. It results in error-cancellation reaction schemes that are automated, general, and can be readily used for a broad range of organic molecules and biomolecules. Herein, we first locate stable conformational and tautomeric forms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…Only a single MP2 calculation To test the accuracy of CBH to get extrapolated CCSD(T) energies, we included all the varied 27 nonaromatic molecules from our earlier test set for obtaining accurate enthalpies of formation 36,37,39 and added glucose (ring and open forms) and alanine dipeptide. 39 The 30 molecule test we assembled ( Figure 6) was further divided into test set A and test set B. Test set A has the 20 common organic molecules, and test set B contains the more challenging systems with ring strain, multiple heteroatoms, or biomolecules with internal hydrogen bonds.…”
Section: A New Concept In Fragment-based Methods As a Results Of Its Mmentioning
confidence: 99%
“…Only a single MP2 calculation To test the accuracy of CBH to get extrapolated CCSD(T) energies, we included all the varied 27 nonaromatic molecules from our earlier test set for obtaining accurate enthalpies of formation 36,37,39 and added glucose (ring and open forms) and alanine dipeptide. 39 The 30 molecule test we assembled ( Figure 6) was further divided into test set A and test set B. Test set A has the 20 common organic molecules, and test set B contains the more challenging systems with ring strain, multiple heteroatoms, or biomolecules with internal hydrogen bonds.…”
Section: A New Concept In Fragment-based Methods As a Results Of Its Mmentioning
confidence: 99%
“…To date, the standard CBH correction scheme has been benchmarked on closed-and open-shell, H,C,N,O,F,S,Clcontaining organic and biomolecules, both neutral and cationic with a wide variety of functional groups. 41,[45][46][47][48][49] Previous performance of CBH on the calculation of the heat of formation of a set of neutral organic molecules from Reference 41 is showcased in Table 4. Using the CBH-3 correction scheme, mean absolute deviations within chemical accuracy are achieved for many different low levels of theory.…”
Section: Performance Of Cbh For Thermochemistrymentioning
confidence: 99%
“…[46] Subsequent applications of CBH on biomolecules have shown that the heats of formation obtained with CBH-2 (vide infra) are in good agreement with computationally expensive Gaussian-n (Gn) and Weizmann-n (Wn) methods for most of the amino acids. [47,48] For a range of organic and bioorganic molecules in these studies, it was observed that the MP2 and CCSD(T) reaction energies were in close agreement for CBH-2 reaction schemes. This allowed the use of MP2 energy and CCSD(T) energies of fragments to extrapolate to the CCSD(T) energy of the target molecule.…”
Section: Introductionmentioning
confidence: 70%
“…It yields accurate thermochemical properties using density functional theory (DFT) methods, as well as wavefunction‐based methods . Subsequent applications of CBH on biomolecules have shown that the heats of formation obtained with CBH‐2 ( vide infra ) are in good agreement with computationally expensive Gaussian‐ n (G n ) and Weizmann‐ n (W n ) methods for most of the amino acids . For a range of organic and bio‐organic molecules in these studies, it was observed that the MP2 and CCSD(T) reaction energies were in close agreement for CBH‐2 reaction schemes.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation